2023
DOI: 10.1101/2023.03.24.534105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glioblastoma induces the recruitment and differentiation of hybrid neutrophils from skull bone marrow

Abstract: Tumor-associated neutrophil (TAN) effects on glioblastoma biology remain under-characterized. We show here that 'hybrid' neutrophils with dendritic features - including morphological complexity, expression of antigen presentation genes, and the ability to process exogenous peptide and stimulate MHCII-dependent T cell activation - accumulate intratumorally and suppress tumor growth in vivo. Trajectory analysis of patient TAN scRNA-seq identifies this phenotype as a polarization state which is distinct from cano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In 2023, Meeki Ld et al. further confirmed the recruitment of TANs from the skull in GBM ( 21 ). They proposed that the role of the skull in supplying immune cells to the GBM TME is pronounced, and that systemic bone marrow sites could not adequately compensate for the absence of skull marrow.…”
Section: The Development Recruitment and Migration Of Neutrophilsmentioning
confidence: 93%
See 1 more Smart Citation
“…In 2023, Meeki Ld et al. further confirmed the recruitment of TANs from the skull in GBM ( 21 ). They proposed that the role of the skull in supplying immune cells to the GBM TME is pronounced, and that systemic bone marrow sites could not adequately compensate for the absence of skull marrow.…”
Section: The Development Recruitment and Migration Of Neutrophilsmentioning
confidence: 93%
“…In 2021, Andrea Cugurra et al demonstrated that neutrophils originated from cranial and vertebral bone marrow can migrate to the meninges and parenchyma via ossified channels containing blood vessels (19, 20). In 2023, Meeki Ld et al further confirmed the recruitment of TANs from the skull in GBM (21). They proposed that the role of the skull in supplying immune cells to the GBM TME is pronounced, and that systemic bone marrow sites could not adequately compensate for the absence of skull marrow.…”
Section: The Development Recruitment and Migration Of Neutrophilsmentioning
confidence: 99%
“…Gliomas can induce peripheral neutrophilia through the secretion of granulocyte-colony stimulating factor (G-CSF) and granulocyte-macrophage colony-stimulating factor (GM-CSF) [68]. Recent work by Lad et al has also demonstrated that GM-CSF in the glioblastoma secretome enhances the longevity of peripheral blood neutrophils [69]. In addition to enhancing granulopoiesis, gliomas can recruit neutrophils to the TME through expression of high levels of IL-8, under stimulation of IL-1, TNFα, and high-mobility group box 1 (HMGB1) derived from NETs [70,71].…”
Section: Neutrophilsmentioning
confidence: 99%
“…However, this anti-tumor effect was lost with tumor progression. Interestingly, Lad et al recently showed that a subset of TANs are recruited from skull marrow and uniquely differentiate into APC-like cells that activate T-cells and suppress tumor growth [69]. A more detailed understanding of neutrophils and other granulocytes and signals that pivot neutrophils to become immunosuppressive may hold promise for a better understanding of the reprogramming system of the TME and new potential immunotherapy targets.…”
Section: Neutrophilsmentioning
confidence: 99%